PREVENTING EFFECT ON DIET-INDUCED OBESITY OFWATER-EXTRACT FROM MASSON PINE POLLEN ON MICE - Geng, Yue; Zhang, Han; Song, Hang; Zhang, Lian; Xu, Jimin; Liu, Ming; Chen, Shanjhan; Han, Lirong (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: In order to investigate the preventing effect of water-extract from masson pine pollen (PWE) on obesity in mice. Materials and Methods: Sixty male KM mice (bodyweight was 19±1g) were divided randomly into six groups: normal control group (NC), high fat group (FC), positive control group (Orlistat, 0.05g/kg bw·d, PC), low-dose PWE group (0.0625g/kg bw·d, PWEL), medium-dose group (0.125g/kg bw·d, PWEM) and high-dose group (0.25g/kg bw·d, PWEH). Mice were treated by intragastric administration daily for 6 weeks. Results: The body weight changes of three PWE groups decreased obviously. In serum, TC of PWEH group reduced remarkably (P<0.05); TG of three PWE groups had significantly declined (P<0.01); HDLC of PWEM and PWEH groups had significantly increased (P<0.05). Leptin level of PWEM and PWEH groups had significantly increased (P<0.01). Adiponectin, resistin level and the activity of CPT-I of PWE groups increased remarkably (P<0.01). Orexigenic peptides NPY and AgRP in serum of PWE groups had significantly declined (P<0.01). Anorexigenic peptides POMC had no difference with each other, and CART had declined. Conclusion PWE could not only promote the absorption and synthesis of fat but also promote the oxidation of fat. Critical was that the oxidation was stronger than the synthesis.